The role of gray-scale ultrasound and elastography in differentiating benign from malignant axillary lymph nodes in patients with breast cancer - Javad Jalili; Abolhassan Shakeri Bavil Olyaei; Hamideh Hosseinpour Feizi; Batoul Siefi; Bahman Mohammadzadeh; Soroush Mostafavi; Armin Zarrintan (Journal of Research in Clinical Medicine, 2023)
Introduction: Breast cancer is one of the most common cancers in women. Involvement of regional lymph nodes by breast cancer has shown to be a significant marker in the overall diagnosis of patients. In this study, we aimed to investigate the role of gray-scale ultrasound and elastography in discriminating benign from malignant axillary lymph nodes in patients with breast cancer. Methods: In this analytical study, patients with breast cancer who were referred to sonography ward of a tertiary medical educational center and found to have suspicious lymph nodes were investigated. Formal properties were evaluated by grayscale ultrasound and tissue properties were assessed by elastography. Biopsies were performed on all cases and suspicious tissues were removed. Results: This study was conducted on 50 patients with the mean age of 48.54±10.58 years. 52% of patients had a mass in their right breast and the most prevalent type of breast cancer was intra-ductal carcinoma. 60% of the lymph nodes were reported to be malignant. In 56% of the lymph nodes, grayscale ultrasound tests demonstrated unusual findings and the most common finding was the removal of fat from lymph node hilum. Moreover, elastography results indicated that 36% of the cases have grade 4 (blue) lesions. Conclusion: This study indicated that grayscale ultrasound and elastography have high sensitivity and specificity in detecting metastatic lymph nodes. This finding was in line with the findings reported in many of the previous studies.